2021
DOI: 10.1097/ccm.0000000000005224
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Assessment of Delirium Severity: The Electroencephalographic Confusion Assessment Method Severity Score (E-CAM-S)

Abstract: OBJECTIVES: Delirium is a common and frequently underdiagnosed complication in acutely hospitalized patients, and its severity is associated with worse clinical outcomes. We propose a physiologically based method to quantify delirium severity as a tool that can help close this diagnostic gap: the Electroencephalographic Confusion Assessment Method Severity Score (E-CAM-S).DESIGN: Retrospective cohort study. SETTING: Single-center tertiary academic medical center. PATIENTS:Three-hundred seventy-three adult pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…We therefore have given maximal points for features that cannot be had in the absence of an appropriate level of consciousness (e.g., negative symptoms) but have not assigned points that can only occur with an appropriate level of consciousness (e.g., positive symptoms of specifically features 7: Perceptual disturbances such as hallucinations and 8: Psychomotor agitation), yielding a score of 15. This practice is consistent with our previously published work, in which patients with coma were assigned maximal CAM-S short form scores (35). Expanded information on evaluation questions and rules used for delirium symptom severity scoring for each category are given in eTables 1 and 2 (http://links.lww.com/CCX/A884).…”
Section: Methodssupporting
confidence: 89%
“…We therefore have given maximal points for features that cannot be had in the absence of an appropriate level of consciousness (e.g., negative symptoms) but have not assigned points that can only occur with an appropriate level of consciousness (e.g., positive symptoms of specifically features 7: Perceptual disturbances such as hallucinations and 8: Psychomotor agitation), yielding a score of 15. This practice is consistent with our previously published work, in which patients with coma were assigned maximal CAM-S short form scores (35). Expanded information on evaluation questions and rules used for delirium symptom severity scoring for each category are given in eTables 1 and 2 (http://links.lww.com/CCX/A884).…”
Section: Methodssupporting
confidence: 89%
“…Furthermore, it is demonstrated that the electrocardiogram (ECG) slowing, such as a composite of generalized theta or delta slowing (OR 10.3, 95% CI, and 5.3–20.1), is associated with delirium severity and poor clinical outcomes ( Kimchi et al, 2019 ). Recently, an automated physiologic process that quantifies the presence and severity of delirium directly has been reported, called the Electroencephalographic Confusion Assessment Method Severity Score (E-CAM-S; van Sleuwen et al, 2022 ). It is based on a learning-to-rank machine learning model of forehead electroencephalography signals, with a level of performance comparable to conventional interview-based clinical assessment.…”
Section: Diagnosismentioning
confidence: 99%
“…Van Sleuwen et al used machine learning to predict the presence and severity of delirium (EEG Confusion Assessment Method severity score; E-CAM-S score) in a heterogeneous ICU population ( n = 373) based on four frontal EEG channels. Severity of delirium was associated with more EEG slowing (increased delta content, reduced alpha content), and E-CAM-S score correlated well with clinical CAM-S as well as with in-hospital mortality [43 ▪ ].…”
Section: Automated Tracking Of Sedation Delirium and Sleep With Elect...mentioning
confidence: 83%